Agricultural destruction of Northern Pintail nests on cropland in prairie Canada - David C. Duncan; James H. Devries (Avian Conservation and Ecology, 2018)
It has been postulated that the decline of the Northern Pintail (Anas acuta) population is related to the propensity of female pintails to nest in cropland. Using spatial modeling at multiple scales, we estimated that the long-term average (1961-2009) breeding population of Northern Pintails in prairie Canada would have initiated a mean of 974,260 nests/year, of which 47% (457,900 +/- 43,270) would have been in cropland. Nest success rates are very low (5%) in spring-seeded cropland with predation and agricultural activity responsible for approximately 78% and 22% of the nest loss, respectively. We estimated that a long-term mean of 94,750 (+/- 19,680) nests representing 524,725 pintail eggs would have been destroyed by agricultural seeding and tillage operations on cropland annually. The number of nests/eggs lost in any given year would vary by an order of magnitude dependent primarily upon the size of the pintail population nesting on the prairies in that year. Our estimate of incidental take is quite robust because it is based on multiple, long-term studies using data from across the Canadian prairies. Our analysis provides additional support for the theory that the pintail's habit of nesting in cropland is the probable reason for the decline in the pintail population, irrespective of the cause of nest loss. Although predation is the primary cause of the loss of pintail nests in cropland, the proportion of nests lost to predation in cropland is similar to that in other upland habitats on the prairies. Thus the additional loss from agriculture could well be incremental and may be the proximate causative factor in the pintail population's decline and failure to recover in recent decades.